CT-guided radiofrequency ablation of spinal osteoblastoma: treatment and long-term follow-up. (3rd April 2018) - Arrigoni, Francesco; Barile, Antonio; Zugaro, Luigi; Fascetti, Eva; Zappia, Marcello; Brunese, Luca; Masciocchi, Carlo
Abstract: Objective: Osteoblastoma (OB) is a painful, rare, benign bone tumour usually observed in young populations, and this condition involves the spine in up to one-third of cases. We sought to focus on the minimally invasive treatment of spinal OB with radiofrequency ablation (RFA) under computed tomography (CT) guidance. When performed near the spinal cord, surgery can lead to instability of the spine, sometimes requiring additional interventions to stabilise the segments involved, and can cause the precocious onset of arthrosis or other degenerative diseases. The results were evaluated both clinically and with the aid of diagnostic imaging techniques during a 5-year follow-up study. Materials and methods: Eleven patients affected by spinal OB were treated in a single session with biopsy and CT-guided RFA. Pre- and post-evaluations of the patients were performed both clinically and with CT and magnetic resonance imaging (MRI). Results: Complete success in terms of pain relief was achieved in all patients. Additional treatments were not required in any patients. There were no complications. During follow-up, neither complications nor pathological findings related to the treatment were observed. Conclusions: Our experience demonstrates that RFA for spinal OB is safe and effective. One of the main advantages of this technique is represented by its lower grade of invasiveness compared with that for potentially hazardous surgical manoeuvres.